Stem cell therapy in dengue virus-infected BALB/C Mice improves hepatic injury - Sakinah, S.; Priya, Sivan Padma; Mok, Pooi Ling; Munisvaradass, Rusheni; Teh, Seoh Wei; Sun, Zhong; Chee, Hui-Yee; Hamat, Rukman Awang; Joseph, Narcisse; Tong, Jia Bei; Kumar, S. Suresh (Frontiers Research Foundation, 2021)
Extensive clinical efforts have been made to control the severity of dengue diseases; however, the dengue morbidity and mortality have not declined. Dengue virus (DENV) can infect and cause systemic damage in many organs, resulting in organ failure. Here, we present a novel report showing a tailored stem-cell-based therapy that can aid in viral clearance and rescue liver cells from further damage during dengue infection. We administered a combination of hematopoietic stem cells and endothelial progenitor cells in a DENV-infected BALB/c mouse model and found that delivery of this cell cocktail had improved their liver functions, confirmed by hematology, histopathology, and next-generation sequencing. These stem and progenitor cells can differentiate into target cells and repair the damaged tissues. In addition, the regime can regulate endothelial proliferation and permeability, modulate inflammatory reactions, enhance extracellular matrix production and angiogenesis, and secrete an array of growth factors to create an enhanced milieu for cell reparation. No previous study has been published on the treatment of dengue infection using stem cells combination. In conclusion, dengue-induced liver damage was rescued by administration of stem cell therapy, with less apoptosis and improved repair and regeneration in the dengue mouse model.